Critical race feminism a reader (Critical America, 2003)
Publisher's description: Critical Race Feminism gives voice to African American, Latina, Asian, Native American, and Arab women, both heterosexual and lesbian. Both a forceful statement and a platform for change, the anthology addresses an ambitious range of subjects, from life in the workplace and motherhood to sexual harassment, domestic violence, and other criminal justice issues. Extending beyond national borders, the volume tackles global issues such as the rights of Muslim women, immigration, multiculturalism, and global capitalism. Revealing how the historical experiences and contemporary realities of women of color are profoundly influenced by a legacy of racism and sexism that is neither linear nor logical, Critical Race Feminism serves up a panoramic perspective, illustrating how women of color can find strength in the face of oppression.